THE CHARACTERISTICS OF CYTOKINE STATUS IN PATIENTS WITH DEEP PHLEGMON OF THE NECK AND SECONDARY ACUTE MEDIASTINITIS UNDER DIFFERENT METHODS OF TREATMENT - M. G. Pustovetova; Yu. V. Chikinev; E. A. Drobyazgin; T. S. Kutepova (Сибирский научный медицинский журнал, 2019)
The aim of the study was to improve the results of treatment of patients with deep neck phlegmon and acute secondary mediastinitis. Material and methods. 81 case histories of patients with deep neck phlegmon and 40 case histories of patients with secondary acute mediastinitis who underwent examination and treatment in the regional clinical hospital, Novosibirsk, for the period from 2007 to 2017 were analyzed. The results of treatment were evaluated by the dynamics  of changes in the serum concentration of pro- and anti-inflammatory cytokines TNF-α, IL-1ß, IL-6, IL-8, IL-4, IL-1β/IL-4. Results and discussion. When applying the method of lavage of deep neck and mediastinum cellular spaces with ozonated 0,9 % sodium chloride solution, there is a 1,2-3-fold faster normalization of cytokine status compared to standard lavage, which indicates a more pronounced decrease in the intensity of the acute inflammatory process in the postoperative period.